MASALAH-MASALAH YANG DI ALAMI SISWA SMK N 5 PEKANBARU - Juita, Ratna; Asyari, Abu; ', Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The objectives of this study are 1) to get the description about personal problem experienced male and female students 2) to get the description about emotional problems experienced by male and female students, 3) to get the information about learning problems experienced by male and female students, 4) to get the information about family problems experienced by male and female students, 5) to get the information about social problem experienced by male and female students, 6) to get the descriptions about the problems of male and female students in some aspects such as personal, emotional learning, family and social, 7) to get the description about the problems experienced by male and female students in general. The mean of collecting data is questioner. The subject of this research is the students of class X and XI that consists of 240 students. The result shows that the problems that experienced by male and female students are different, the research finding as stated in table 5 shows that male students who have family problem are 93,2% and female students also have the same problem but it is higher than male students’ problem, that is 98% in Senior Vocational School Number 5 Pekanbaru. It s known that the students class XI of Senior Vocational School Number 5 Pekanbaru have family problems on the average. The impact of the family problem is in few category.Keywords: Problems